Clinical characteristics and prognosis of 272 postterm choriocarcinoma patients at Peking Union Medical College Hospital: a retrospective cohort study. Issue 1 (December 2016) - Li, Jie; Yang, Junjun; Liu, Pengfei; Ren, Tong; Zhao, Jun; Feng, Fengzhi; Wan, Xirun; Xiang, Yang
Abstract Background The objective of our study was to investigate the clinical characteristics and prognosis of postterm choriocarcinoma patients at Peking Union Medical College Hospital within the past 30 years. Methods The clinical characteristics and pertinent follow-up data of 272 patients with postterm choriocarcinoma diagnosed from December 1985 through December 2014 in our hospital were reviewed. The clinical characteristics of two cohorts cut off at 2006 were compared usingχ 2 tests. Risk factors of prognosis were estimated by multivariate Cox proportional regression analysis. Results The most common initial symptom was abnormal uterine bleeding. After individualized treatment 239 patients (87.9 %) achieved complete remission, including 140 patients received initial treatment of 5-fluorouracil-based multidrug chemotherapy. There were almost no statistically significant differences in the clinical characteristics and survival rates between the two cohorts. The results of the multivariate analysis showed that history of resistance to multidrug chemotherapy, liver metastasis and FIGO score greater than 12 were independent risk factors of prognosis. Conclusions Postterm choriocarcinoma patients were usually accompanied by several high-risk factors that should received combined chemotherapy to prevent delay in adequate treatment. 5-fluorouracil-based multidrug chemotherapy, which has been applied at PUMCH for several decades, can be an effective initial treatment for postterm choriocarcinoma patients. More emphasis should be placed on those who have history of resistance to multidrug chemotherapy, liver metastasis or a FIGO score greater than 12.